BEZPIECZEŃSTWO POLSKI W OKRESIE TRANSFORMACJI SYSTEMOWEJ - SZCZUREK Tadeusz (2011)
The article presents the social and political situation of Poland in the context of changes, resulting from the downfall of the so-called „Eastern bloc” after year 1989. Particular emphasis was put on the significance of the following historic events: dissolution of the Warsaw Pact; withdrawal of the Russian army from Poland; Poland becoming a member of the North Atlantic Treaty Organization and the European Union and the terrorist attack on World Trade Center of September 11th, 2001. In the context of these events, on the basis of source documents (assumptions, doctrines and strategies), the strategic directions of building of a state security system were presented.